New approach for the synthesis of water soluble fac-[MI(CO)3]+ bis(diarylphosphino)alkylamine complexes (M = 99Tc, Re). Issue 47 (8th November 2021) - Kama, Dumisani V.; Frei, Angelo; Brink, Alice; Braband, Henrik; Alberto, Roger; Roodt, Andreas
Abstract : A new approach for the synthesis of water soluble fac -[M I (CO)3 ] + bis (diarylphosphino)alkylamine complexes (M = 99 Tc, Re) is presented. Abstract : A novel proof-of-concept is reported to modify the water solubility and potential biological effects of a bis(diphenylphosphino)alkylamine (PNP) ligand and the corresponding metal complex, by introducing an amine group on the outer periphery of the pendant ligand arm. Thus, a tertiary butoxycarbonyl protected N '-Boc-ethylenediamine- N, N -bis(diphenylphosphino) ( N '-Boc-PNP) ligand (1 ) was synthesized by reacting the protected ethylenediamine and chlorodiphenylphosphine in a 1 : 2 molar ratio. The corresponding fac -[Re(CO)3 ( N '-Boc-PNP)Br] (1A ) complex was then obtained by reacting N '-Boc-PNP (1 ) with (Et4 N)2 fac -[Re(CO)3 Br3 ] in equimolar amounts in DCM at 50 °C. De-protection of the N '-Boc pendant amine group in 1A with TFA leads to fac -[Re(NH3 + -PNP)(CO)3 Br]·CF3 COO − (1B ) which is soluble in D2 O (>0.05 M). Treating 1B with saturated aqueous NaHCO3 yields fac -[Re(NH2 -PNP)(CO)3 Br]·MeOH (1C ) in near quantitative yield. Although both 1A and 1C are not soluble in D2 O, addition of TFA easily generates 1B ( 31 P NMR), confirming the formation of the protonated amine. Isolation of fac -[ 99 Tc(CO)3 ( N -Boc-PNP)(Cl)] (1D ) confirmed that the rhenium and technetium ( 99 Tc) can be easily interchanged in this process. Reported are hence the unique rhenium series of compounds 1A, 1B and 1C and the corresponding technetium complex 1D, unequivocally characterized by single crystal XRD, as well as IR and 1 H NMR spectroscopy. Preliminary antimicrobial evaluation indicates that ligand 1 and its respective rhenium complexes (1A–1C ) were not active against selected fungi ( Candida albicans and Cryptococcus neoformans ) and bacteria ( Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Staphylococcus aureus ). These types of ligands and complexes therefore present themselves as excellent radio models for further evaluation using 186 Re, 188 Re and 99m Tc to potentially study the radio toxicity of appropriately designed complexes.